Model-based analysis for the thermal management of open-cathode proton exchange membrane fuel cell systems concerning efficiency and stability. (November 2016) - Strahl, Stephan; Costa-Castelló, Ramon
Abstract : Highlights: Operation point characterization. Linearized models. Temperature-dependent maximum power in the moderate temperature region. Maximum power is located at the stability limit in the phase plane. Simulation results serve for the design of optimal thermal management strategies. The maximum eigenvalue is approximately 10 times smaller than the minimum eigenvalue. Abstract: In this work we present a dynamic, control-oriented, concentrated parameter model of an open-cathode proton exchange membrane fuel cell system for the study of stability and efficiency improvement with respect to thermal management. The system model consists of two dynamic states which are the fuel cell temperature and the liquid water saturation in the cathode catalyst layer. The control action of the system is the inlet air velocity of the cathode air flow manifold, set by the cooling fan, and the system output is the stack voltage. From the model we derive the equilibrium points and eigenvalues within a set of operating conditions and subsequently discuss stability and the possibility of efficiency improvement. The model confirms the existence of a temperature-dependent maximum power in the moderate temperature region. The stability analysis shows that the maximum power line decomposes the phase plane in two parts, namely stable and unstable equilibrium points. The model is capable of predicting the temperature of a stable steady-state voltage maximum and the simulation results serve for the design of optimal thermal management strategies.